Hydrodynamic Research of Marine Structures - Dimitrios N. Konispoliatis; Spyros A. Mavrakos (Journal of Marine Science and Engineering)
Hydrodynamics plays a crucial role in the design and analysis of marine structures, as it involves the study of the motion of fluid and its interaction with various types of structures in a marine environment [...]